Occurrence and Antimicrobial Susceptibility of Campylobacter jejuni and C-coli in Dog Feces from Public Parks in Southern Ecuador - Simaluiza Masabanda, R. (2017)
Background: Campylobacter jejuni and C. coli are important agents of diarrhea in human beings. Several animals are reservoirs for these bacteria and they may contribute to environmental contamination through fecal shedding. The presence of dog feces in urban settings could be a risk of Campylobacter environmental contamination and a problem of public health concern. Besides environmental contamination, the increasing antimicrobial resistance among Campylobacter is another issue of public health significance. The aims of this study were to determine the prevalence of C. jejuni and C. coli in dog feces collected from public parks of Loja city, Ecuador, and establishing their susceptibility to six antibiotics.